2012
DOI: 10.1186/1471-2415-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Eye care utilization by older adults in low, middle, and high income countries

Abstract: BackgroundThe risk of visual impairment increases dramatically with age and therefore older adults should have their eyes examined at least every 1 to 2 years. Using a world-wide, population-based dataset, we sought to determine the frequency that older people had their eyes examined. We also examined factors associated with having a recent eye exam.MethodsThe World Health Surveys were conducted in 70 countries throughout the world in 2002-2003 using a random, multi-stage, stratified, cluster sampling design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 33 publications
6
63
4
1
Order By: Relevance
“…In surveys in Australia, Canada and the USA, a similar proportion (60-70%) of older adults had visited an eye-care provider, although not necessarily an optometrist, in the previous year. 142 Data from the Optical Confederation survey for 2011/12 give an average interval between eye examinations of 27 months overall and 30 months for those of working age, 52 which is broadly consistent with findings in PrOVIDe (see Figures 9 and 10).…”
Section: Intervals Between Eye Examinations and Spectacle Dispensingsupporting
confidence: 74%
“…In surveys in Australia, Canada and the USA, a similar proportion (60-70%) of older adults had visited an eye-care provider, although not necessarily an optometrist, in the previous year. 142 Data from the Optical Confederation survey for 2011/12 give an average interval between eye examinations of 27 months overall and 30 months for those of working age, 52 which is broadly consistent with findings in PrOVIDe (see Figures 9 and 10).…”
Section: Intervals Between Eye Examinations and Spectacle Dispensingsupporting
confidence: 74%
“…This is in agreement with reports from other countries (2,3,5,7,9,11,12,23-25,33). Nevertheless, in contrast to other studies, (5,7,9,24,25) gender inequality was more serious in our study, where women were seen to be more deprived of eye care services than men. This difference was significant in simple as well as multiple logistic regression models.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies on inequality have indicated that blindness is more prevalent in poor communities (17)(18)(19); gender disparity in eye diseases and access to eye care services has also been reported (20)(21)(22). Although reports of disparity in the frequency of utilization of eye care services (23)(24)(25) are available, we found no report on the role of economic inequality in utilization of eye care services. The goals of vision 2020 will undoubtedly be made easier by understanding the extent of this disparity and its determinants.…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Similar absence of ophthalmological care were described recently only in low income countries from South Asia and Africa [24], and particularly in very isolated locations or in critical conditions. [25,26] When marginalized groups located in urban areas from developed countries are studied, access to eye care is substantially higher.…”
Section: Discussionmentioning
confidence: 78%